The influence of cardiorespiratory fitness level on the relationship between work rates at the aerobic threshold (AerT) and the point of maximal fat oxidation (Fatmax) in untrained adults - Martin Pühringer; Susanne Ring-Dimitriou (Frontiers Media S.A., 2024)
IntroductionIn this study, we investigated the impact of cardiorespiratory fitness (CRF), quantified as peak oxygen consumption (VO2peak), on the relationship between work rates (WR) at the aerobic threshold (AerT) and the point of maximal fat oxidation rate (Fatmax).MethodsA total of 761 untrained adults aged 41-68 completed a one-minute incremental exercise test on a cycle ergometer, using breath-by-breath gas analysis to determine VO2peak, AerT, and Fatmax. AerT was determined using automatic and visual detection methods, and Fatmax was determined using indirect calorimetry. Participants were categorized into CRF-groups: low (<25th percentile), medium (≥25th percentile and <75th percentile), and high (≥75th percentile).ResultsFatmax was found at 43 ± 7% WRpeak, 37% ± 6% WRpeak and 35% ± 7% WRpeak in the low, medium, and high CRF-groups, respectively. In contrast, AerT was located at significantly higher relative work rates: 51% ± 8% WRpeak, 47% ± 10% WRpeak, and 47% ± 11% WRpeak in the respective CRF-groups. There was a weak agreement between Fatmax and AerT [intraclass correlation coefficient (ICC) = .19, p < .001], and the ICC decreased from .35 to .12 to .13, while the mean bias ±95% limits of agreement increased from 8% ± 14% WRpeak to 8% ± 19% WRpeak to 12% ± 44% WRpeak from CRF-low to CRF-medium to CRF-high. The mean difference between Fatmax and AerT was significantly different among the CRF subgroups: 8% ± 7% WRpeak vs. 10% ± 10% WRpeak vs. 12% ± 11% WRpeak in low, medium, and high CRF-groups, respectively. Nonetheless, multiple regression analysis revealed only a weak positive correlation between the difference in relative work rates (% WRpeak) between Fatmax and AerT (dependent variable) and the predictor variables CRF and sex, both identified as significant (R = .19, p < .001).ConclusionOur study confirms substantial differences in exercise intensities between Fatmax and AerT in untrained adults (10% ± 19% WRpeak, ranging from −14% to 53% WRpeak). Importantly, this difference remains relatively consistent across varying CRF levels, emphasizing the distinct nature of Fatmax and AerT, with CRF playing a limited role in influencing their relationship in our study's untrained adults.